Eksposisi Teologis Kolose 2:8–10 Terhadap Sinkretisme Iman di Kalangan Masyarakat Kristen Desa Teluk Runjai - Nababan, Jekson Sharon (Riviera Publishing, 2025)
The phenomenon of faith syncretism is still a challenge for churches in various cultural contexts, including in Teluk Runjai Village, West Kalimantan. Although most people have embraced Christianity, belief in spirits, shamans, and spiritual customs has persisted. This study aims to examine these dynamics through the theological exposition of Colossians 2:8–10 and analyze them in the context of contextual evangelical theology. The research approach used was a qualitative case study, with data collection through in-depth interviews, participatory observations, and documentation of 4 participants representing Christians, church leaders, and indigenous leaders. The data were analyzed thematically-reflectively to find patterns of faith meaning, spiritual fear, and religious experiences of the community. The results of the study reveal four main themes: fear of dark powers, the role of shamans as spiritual mediators, conflicts between faith and customs, and a new awareness of the power of Christ. These findings show that faith syncretism in Runjai Bay stems not only from doctrinal errors, but also from the absence of contextual theological ministry. Theoretically, this study expands the contextual evangelical theological discourse and offers a text-based model of faith transformation of Colossians 2:8–10; Practically, this research encourages the church to develop faith-building ministries that free people from spiritual fear and affirm faith in the power of Christ.